1985
DOI: 10.1007/bf00235875
|View full text |Cite
|
Sign up to set email alerts
|

The distal hindlimb musculature of the cat

Abstract: In order to better understand the organization of the locomotor control system, we examined the temporal patterns of distal hindlimb muscle responses to brief electrical stimulation of cutaneous nerves during walking on a treadmill. Electromyographic recordings were made from twelve muscles; stimuli were applied individually to three nerves at random times throughout the step cycle. A new graphical technique was developed to assist detailed examination of the time course and gating of complex reflex patterns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 25 publications
7
37
1
Order By: Relevance
“…Our results also do not exclude the possibility that a net speed-dependent inhibition might exist for movements performed at greater speeds than galloping, for example, during a paw shake or a scratch response; i.e. movements that are performed at frequencies of 5-10·Hz (Smith et al, 1980;Abraham and Loeb, 1985;Fowler et al, 1988; M. Kaya, T. Leonard and W. Herzog, unpublished observations). It has been suggested that SOL activity is strongly inhibited by increasing MG force in decerebrate cats (Nichols, 1994).…”
Section: Effect Of Speed and Intensity Of Locomotion On The Modulationcontrasting
confidence: 62%
See 2 more Smart Citations
“…Our results also do not exclude the possibility that a net speed-dependent inhibition might exist for movements performed at greater speeds than galloping, for example, during a paw shake or a scratch response; i.e. movements that are performed at frequencies of 5-10·Hz (Smith et al, 1980;Abraham and Loeb, 1985;Fowler et al, 1988; M. Kaya, T. Leonard and W. Herzog, unpublished observations). It has been suggested that SOL activity is strongly inhibited by increasing MG force in decerebrate cats (Nichols, 1994).…”
Section: Effect Of Speed and Intensity Of Locomotion On The Modulationcontrasting
confidence: 62%
“…Therefore, a substantial increase in SOL force above that obtained for slow walking is only possible if activation goes towards maximum, or if the muscle is stretched at full activation. Although the size principle of motor unit recruitment is not applicable across muscles, but only within a given muscle (see paw-shake response in cat SOL and MG; Smith et al, 1980;Abraham and Loeb, 1985), it is feasible to assume that the 95-100% slow SOL is recruited to a much greater extent for standing and slow walking than the 70-80% fast MG. Consequently, there is less room for SOL force and activity modulation from the slow walking baseline, compared to MG force and activity modulation.…”
Section: Modulation Of Mg and Sol Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many activation patterns that would match the intended endpoint force pattern. Our choice of activations emphasized the deeper antigravity muscles -soleus and VI -while keeping the average activation level low (Sherrington, 1910;Abraham & Loeb, 1985;Roy et al, 1991). Changes in initial activation on the order of 10-15% had little effect on the qualitative results.…”
Section: Discussionmentioning
confidence: 99%
“…The initial activation pattern (table 1) was chosen to mimic the pattern of stance activation, i.e. predominantly the deep, "slow" anti-gravity muscles, (Roy et al, 1991;Abraham & Loeb, 1985) and to result in a stance-like force at the toe (Macpherson, 1994). The choice of initial activations is clearly critical to the results presented here, and little direct data are available.…”
Section: Reflex Evaluationmentioning
confidence: 99%